Biochemical characterization of a novel oxidatively stable, halotolerant, and high‐alkaline subtilisin from Alkalihalobacillus okhensis Kh10‐101T. Issue 10 (6th July 2022) - Falkenberg, Fabian; Rahba, Jade; Fischer, David; Bott, Michael; Bongaerts, Johannes; Siegert, Petra
Abstract : Halophilic and halotolerant microorganisms represent a promising source of salt‐tolerant enzymes suitable for various biotechnological applications where high salt concentrations would otherwise limit enzymatic activity. Considering the current growing enzyme market and the need for more efficient and new biocatalysts, the present study aimed at the characterization of a high‐alkaline subtilisin from Alkalihalobacillus okhensis Kh10‐101 T . The protease gene was cloned and expressed in Bacillus subtilis DB104. The recombinant protease SPAO with 269 amino acids belongs to the subfamily of high‐alkaline subtilisins. The biochemical characteristics of purified SPAO were analyzed in comparison with subtilisin Carlsberg, Savinase, and BPN'. SPAO, a monomer with a molecular mass of 27.1 kDa, was active over a wide range of pH 6.0–12.0 and temperature 20–80 °C, optimally at pH 9.0–9.5 and 55 °C. The protease is highly oxidatively stable to hydrogen peroxide and retained 58% of residual activity when incubated at 10 °C with 5% (v/v) H2 O2 for 1 h while stimulated at 1% (v/v) H2 O2 . Furthermore, SPAO was very stable and active at NaCl concentrations up to 5.0 m . This study demonstrates the potential of SPAO for biotechnological applications in the future. Abstract : A subtilisin‐type protease from Alkalihalobacillus okhensis Kh10‐101 T was cloned and expressed in Bacillus subtilis DB104. The comprehensive biochemical characterization revealed a resilient protease with high stability against hydrogen peroxide 5% (v/v) and activity at NaCl concentrations up to 5.0 m . The activity over a wide range of pH and temperature demonstrates the potential for biotechnological applications.